Ethical Climate In Vocational Program Administrative Sciences Department: Student Perception (Issues in Social and Environmental Accounting (ISEA), 2013)
The existence of ethics course in the designed curriculum given, expected to shape morale and develop ethic awareness between student in their study environment. This thing will be a primary asset for graduate candidates in the future. This research is an effort to make an image about study environment climate, that occur in Vocational Program generally, and in Administration Science particularly. The aim of this study is to describe students’ perceptions of their institution’s ethical environment. The Ethical Climate Questionnaires were completed by fifty two final-year vocational program students. The result showed that the type of consensual morality is the most dominant factor that forms ethical environment in campus.